An Algorithm for nth Order Intgro-Differential Equations by Using Hermite Wavelets Functions - Baghdad Science Journal (مجلة بغداد للعلوم)
In this paper, the construction of Hermite wavelets functions and their operational matrix of integration is presented. The Hermite wavelets method is applied to solve nth order Volterra integro diferential equations (VIDE) by expanding the unknown functions, as series in terms of Hermite wavelets with unknown coefficients. Finally, two examples are given